Sophie's squash go to school - Miller, Pat Zietlow (Schwartz & Wade Books, 2016)
On her very first day of school, Sophie is reluctant to make friends with the other children, preferring to play with two squash she grew in her garden--but when a particularly persistent boy named Steven gives her a packet of seeds as an apology for accidentally ripping her picture, she realizes that it just takes time to grow a friend.